2017
DOI: 10.1111/jphp.12741
|View full text |Cite
|
Sign up to set email alerts
|

Hypericum perforatum L. supplementation protects sciatic nerve injury-induced apoptotic, inflammatory and oxidative damage to muscle, blood and brain in rats

Abstract: HPL may play a role in preventing SNI-induced inflammatory, oxidative and apoptotic blood, muscle and brain damages through upregulation of the GSH and GPx values but downregulation of PARP, caspase level and cytokine production in SNI-induced rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 45 publications
1
19
0
1
Order By: Relevance
“…Antioxidant and ROS scavenger effects of HP both in DRGN of SCI-induced rats (Uchida et al, 2008; Nazıroğlu et al, 2014a) and neutrophil of patients with inflammatory diseases (Nazıroğlu et al, 2014b,c) were reported. Recently, we observed modulator role of HP on apoptotic, inflammatory and oxidative stress values in muscle, blood and brain of SNI-induced rats (Uslusoy et al, 2017). Therefore, HP may attenuate oxidative stress, apoptosis and Ca 2+ entry through modulation of TRPM2 and TRPV1 in DRGN and sciatic neurons of SNI-induced rats.…”
Section: Introductionmentioning
confidence: 90%
“…Antioxidant and ROS scavenger effects of HP both in DRGN of SCI-induced rats (Uchida et al, 2008; Nazıroğlu et al, 2014a) and neutrophil of patients with inflammatory diseases (Nazıroğlu et al, 2014b,c) were reported. Recently, we observed modulator role of HP on apoptotic, inflammatory and oxidative stress values in muscle, blood and brain of SNI-induced rats (Uslusoy et al, 2017). Therefore, HP may attenuate oxidative stress, apoptosis and Ca 2+ entry through modulation of TRPM2 and TRPV1 in DRGN and sciatic neurons of SNI-induced rats.…”
Section: Introductionmentioning
confidence: 90%
“…In another experimental study where especially the sciatic nerve damage was shown, it was observed that IL-1β levels significantly increased in trauma group compared to the control group [20][21][22]. In another study prepared based on sciatic nerve damage model, TNF-α, IL-1β, and IL-10 values increased significantly compared to the control group [6,3]. These markers cause neuroinflammationdependent cascade to start and worsen things after nerve damage.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β and TNF-α are important cytokines which are released from glial cells, and they play a key role in chronic pain, memory and damage pathogenesis. It was observed that sciatic nerve damage in the environment increased starting from the fifth hour following nerve damage [5,6,3]. Cytokines such as IL-1β and TNF-α were used to determine the anti-inflammatory effect in different experimental models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations